2016
DOI: 10.1016/j.trd.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Technical and environmental effects of biodiesel use in local public transport

Abstract: Biodiesel use in local public transport could be especially significant in improving air quality in cities. The purpose of the experiments described in this paper was to evaluate the various (10, 20 and 50%) blends of biodiesel with diesel in the context of the engine and pollution aspects. As regards the experimental use of these findings on municipal buses, these experiments were the first reference in Hungary. The ages (15-20 years) and types of buses (Ikarus-280, Ikarus-260) used in the experiments are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…However, the authors failed to offer any explanations about the CO2 reduction observed in their study. The results obtained by Bai et al (2016) were also in line with those of the present study. More specifically, they also reported a decrease in CO and HC emissions when using B10, B20, and B50 (compared with the emissions recorded for B4) on urban busses under idle operation mode.…”
Section: Real-world Operation Test Results: Idle-emissionssupporting
confidence: 93%
“…However, the authors failed to offer any explanations about the CO2 reduction observed in their study. The results obtained by Bai et al (2016) were also in line with those of the present study. More specifically, they also reported a decrease in CO and HC emissions when using B10, B20, and B50 (compared with the emissions recorded for B4) on urban busses under idle operation mode.…”
Section: Real-world Operation Test Results: Idle-emissionssupporting
confidence: 93%
“…On the other hand, this result also indicates that among all the sectors in Beijing, the tourism industry was the important emitter and, therefore, should be especially targeted in mitigation policies. Promising measures are enhancing the share of cleaner fossil fuels such as natural gas in the accommodation and food sector [54], using biodiesel in transportation sector [57] and adopting economic instruments such as taxes or subsidies [58]. For the total CO 2 emissions structure of the tourism industry, the transportation sector (S1) was the largest contributor (38.43%) in 2007, while the accommodations and food sector (S3) became the largest contributor (40.90%) in 2012.…”
Section: The Co 2 Emissions Of the Tourism Industrymentioning
confidence: 99%
“…Another example is the application of maintenance tools (e. g. repair). In the case of Hungarian infrastructure, a lot of transportation and building stocks are over their originally planned life cycle [46,47]. Even though the circular priorities prefer to maintain the function of products, the improvement of obsolete systems can easily lead to major deadweight losses in the long-term [48,49,50].…”
Section: Priority Levels For Circular Solutionsmentioning
confidence: 99%